Investigating the effects of prompt characteristics on the comparability of TOEFL iBT™ integrated writing tasks. (October 2013) - Cho, Yeonsuk; Rijmen, Frank; Novák, Jakub
This study examined the influence of prompt characteristics on the averages of all scores given to test taker responses on the TOEFL iBT TM integrated Read-Listen-Write (RLW) writing tasks for multiple administrations from 2005 to 2009. In the context of TOEFL iBT RLW tasks, the prompt consists of a reading passage and a lecture. To understand characteristics of individual prompts, 107 previously administered RLW prompts were evaluated by participants on nine measures of perceived task difficulty via a questionnaire. Because some of the RLW prompts were administered more than once, multilevel modeling analyses were conducted to examine the relationship between ratings of the prompt characteristics and the average RLW scores, while taking into account dependency among the observed average RLW scores and controlling for differences in the English ability of the test takers across administrations. Results showed that some of the variation in the average RLW scores was attributable to differences in the English ability of the test takers that also varied across administrations. Two variables related to perceived task difficulty, distinctness of ideas within the prompt and difficulty of ideas in the passage, were also identified as potential sources of variation in the average RLW scores.